Development and optimization of ultrasonic extraction of total phenols from fresh peel of Pouteria caimito and its bioactivity evaluation - Li, Jiaojiao; Jiang, Zheng; Li, Xinxin; Gao, Xun; Shen, Jinyang; Liu, Qiang; Xu, Ruibo (Italian Journal of Food Science, 2025)
This paper used peel, a by-product of Pouteria caimito, as raw material to extract total phenols from peel by ultrasonic. To avoid the damage of polyphenol oxidase to the total phenolic content (TPC) of the pericarp, the effects of different pretreatment methods on the yield of the total phenolic content of the pericarp were discussed in the Pre-experiment. The optimal pretreatment conditions were determined as follows: blanching the peel for 3 min, adding Na2SO3 (1 %, solid-liquid ratio 1:1); Under these conditions, the TPC of peel increased from 4.022 ± 0.02 mg/g without treatment to 10.40 ± 0.20 mg/g. Based on single-factor experiments and response surface methodology, the optimal extraction process was determined as follows: EtOH concentration 13 %, solid-liquid ratio 1:30, ultrasonic time 50 min, extraction temperature 29 ℃, extraction for 4 times; Under this condition, the TPC in P. caimito peel was 17.08 ± 0.39 mg/g. The purity of the total phenol extract reached 30 % after purification by AB-8 resin. In vitro activity analysis showed that the purified had a scavenging rate of 96.05% and 100% for DPPH and ABTS at a mass concentration of 1.75 mg/mL and 3.75 mg/mL, respectively, at concentrations of 4 mg/mL and 5.5 mg/mL, it demonstrated a complete inhibitory effect on tyrosinase and acetylcholinesterase. Utilizing UPLC-HRMS, 56 compounds were successfully identified within the purified product. Three key compounds (Quercetin, Ferulic acid and Isorhamnetin) were screened through network pharmacology, and it was predicted that these compounds could treat Alzheimer’s disease through the cholinergic synaptic pathway. Molecular docking technology further revealed the effects of CPP on AChE. This study presents a promising avenue for developing natural antioxidants, TYR inhibitors, and AChE inhibitors in both the food and pharmaceutical industries.